2020
DOI: 10.1038/s41416-019-0725-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VEGF therapy resistance in ovarian cancer is caused by GM-CSF-induced myeloid-derived suppressor cell recruitment

Abstract: Background The mechanism of resistance development to anti-VEGF therapy in ovarian cancer is unclear. We focused on the changes in tumour immunity post anti-VEGF therapy. Methods The frequencies of immune cell populations and hypoxic conditions in the resistant murine tumours and clinical samples were examined. The expression profiles of both the proteins and genes in the resistant tumours were analysed. The impact of granulocyte–monocyte colony-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…Particularly, immune, lactate and ROS metabolism microenvironment, and acidic niche are well-known top-affected TMEs. Hypoxia-induced VEGF expression is a typical product of the reshaping of immune microenvironment 96 Horikawa et al 136 , 137 Sonveaux et al 101 demonstrated a phenomenon called “glycolytic switch” and “metabolic symbiosis”, and stated that oxidative cancer cells prefer utilizing lactate rather than glucose, in which MCT1 mediates a lactate exchange in tumors. 138 Hypoxic cells consume glucose and produce lactate, which can diffuse based on the concentration gradient, whereas oxidative cancer cells uptake lactate via MCT1.…”
Section: Crosstalk and Nexus Among Specialized Microenvironmentsmentioning
confidence: 99%
“…Particularly, immune, lactate and ROS metabolism microenvironment, and acidic niche are well-known top-affected TMEs. Hypoxia-induced VEGF expression is a typical product of the reshaping of immune microenvironment 96 Horikawa et al 136 , 137 Sonveaux et al 101 demonstrated a phenomenon called “glycolytic switch” and “metabolic symbiosis”, and stated that oxidative cancer cells prefer utilizing lactate rather than glucose, in which MCT1 mediates a lactate exchange in tumors. 138 Hypoxic cells consume glucose and produce lactate, which can diffuse based on the concentration gradient, whereas oxidative cancer cells uptake lactate via MCT1.…”
Section: Crosstalk and Nexus Among Specialized Microenvironmentsmentioning
confidence: 99%
“…As mentioned above, GM-CSF promotes monocyte production both in the bone marrow and in the spleen. Accordingly, GM-CSF blockade in mice inhibited tumor-induced mobilization of CD11b + Gr1 + myeloid cells, resulting in enhanced antitumor T-cell responses (136,137). The CD11b + Gr1 + cell subset comprises a heterogenous mixture of monocytes and granulocytes, therefore determining the impact of GM-CSF neutralization specifically on monocytes will require further investigation.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Thus, B cells and regulatory T cells build innate cytotoxic lymphocytes, immunosuppressive microenvironment, and NKT and natural killer cells (NK) cells lead to the immunostimulant TME (Balato et al., 2009 ; Vivier et al., 2012 ; Krijgsman et al., 2018 ). The improved expression of GM-CSF and VEGF induces the formation of myeloid-derived suppressive cells (MDSCs) at the bone marrow, which is deployed to the TME while cells stay undifferentiated (Vetsika et al., 2019 ; Horikawa et al., 2020 ). MDSCs are generally associated with bad prognosis as they include angiogenesis and inhibition CD8 + cytotoxic T cells and NK cells (Horikawa et al., 2020 ).…”
Section: Challenges Offered By Tme To Nanomedicinementioning
confidence: 99%
“…The improved expression of GM-CSF and VEGF induces the formation of myeloid-derived suppressive cells (MDSCs) at the bone marrow, which is deployed to the TME while cells stay undifferentiated (Vetsika et al., 2019 ; Horikawa et al., 2020 ). MDSCs are generally associated with bad prognosis as they include angiogenesis and inhibition CD8 + cytotoxic T cells and NK cells (Horikawa et al., 2020 ).…”
Section: Challenges Offered By Tme To Nanomedicinementioning
confidence: 99%